The Daughter of Time: Late Development of Waldenstrom’s Macroglobulinemiain a Patient with Immunotactoid Glomerulopathy. - Gabbay, Ezra; Shavit, Linda; Ganzel, Chezi; Friedmann, Reuven; Kharenko, Oleg; Sara Shapiro, Dvorah; Slotki, Itzchak (Journal of Hematology and Oncology Research, 2015)
Immunotactoid glomerulopathy (ITG) is a rare cause of chronic kidney disease (CKD) and end-stage-renal-disease (ESRD). It is often associated with monoclonal gammopathy and/or hematologic malignancy. We report a patient originally diagnosed with ITG in 1998. He presented with nephrotic-range proteinuria, hypertension, and a gradual decline in glomerular filtration rate. A published case report of this patient at the time the disease was originally diagnosed described only a small peak of IgM paraprotein without lymphoma or plasma cell dyscrasia. He was diagnosed with monoclonal gammopathy of unknown significance. He later developed ESRD and initiated hemodialysis in 2004. Fourteen years after the diagnosis of ITG and MGUS was made he developed headache, lymphadenopathy, borderline splenomegaly, thrombocytopenia, and coagulopathy. Workup revealed a very high level of monoclonal IgM-kappa (4390 mg/dL),and low grade B-cell lymphoma, consistent with lymphoplasmacytic lymphoma, leading to a diagnosis of Waldenstrom’s macroglobulinemia (WM). He died shortly thereafter of complicated gram-negative sepsis. To our knowledge this is the first report of WM associated with ITG. The patient's course illustrates that plasma cell dyscrasia and lymphoma can present many years after the original diagnosis of ITG is made and that continued vigilance for these conditions is warranted.
Keywords: Immunotactoid Glomerulopathy; Waldenstrom Macroglobulinemia; Lymphoplasmacytic Lymphoma; End-Stage Renal Disease; Monoclonal Gammopathy; Chronic Kidney Disease